2018
DOI: 10.3389/fmicb.2018.02919
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Common Respiratory Viral Infections and Identification of Adenovirus in Hospitalized Adults in Harbin, China 2014 to 2017

Abstract: Background: Respiratory infections pose a great challenge in global health, and the prevalence of viral infection in adult patients has been poorly understood in northeast China. Harbin is one of the major cities in northeast China, and more than half of any given year in Harbin is occupied by winter. To reveal the viral etiology and seasonality in adult patients from Harbin, a 4-year consecutive survey was conducted in Harbin, China.Methods: From January 2014 to December 2017, specimens were obtained from adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
0
8
1
Order By: Relevance
“…Adenovirus infections can occur endemically throughout the year. Contrary to previous reports, [14][15][16] this study showed that summer and winter were the predominant epidemic seasons in Chongqing, China. The differences in seasonal epidemic occurrence were likely due to different serotypes and variations in climates between different countries or regions.…”
Section: Discussioncontrasting
confidence: 99%
“…Adenovirus infections can occur endemically throughout the year. Contrary to previous reports, [14][15][16] this study showed that summer and winter were the predominant epidemic seasons in Chongqing, China. The differences in seasonal epidemic occurrence were likely due to different serotypes and variations in climates between different countries or regions.…”
Section: Discussioncontrasting
confidence: 99%
“…This is similar to the findings of Wu et al We speculate that the high positive rate of ADV in children 3-6 years of age was because they were in kindergarten in Hangzhou and prone to cross-infection. According to another study on ADV prevalence in adults in Harbin, China, ADV incidence typically was highest in the spring, followed by winter [ 17 ]. A study conducted in Mainz, Germany [ 18 ], showed a negative correlation between ADV infection and temperature, which was similar to the results reported in Harbin.…”
Section: Discussionmentioning
confidence: 99%
“…IFA and real-time PCR offer advantages in terms of speed, and the diagnosis of HAdV infection can be completed within 2 h[16, 18]. Detection of HAdVs in nasopharyngeal swab samples by IFA is well-established and commonly used[19]. Monoclonal antibodies (mAbs) employed by IFA to detect HAdVs should ideally target highly conserved epitope types.…”
Section: Introductionmentioning
confidence: 99%